2015
DOI: 10.1521/jscp.2015.34.4.322
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Mnemic Neglect Among Socially Anxious Individuals

Abstract: This is an article that was published in the Journal of Social and Clinical Psychology. The version of record can be found here: http://guilfordjournals.com/doi/abs/10.1521/jscp.2015.34.4.322The relation between social anxiety and memory for self-threatening information was investigated in the context of the mnemic neglect paradigm (Sedikides & Green, 2000). It was hypothesized that those high in social anxiety would evince a loss of mnemic neglect: They would show a reduced likelihood of poor memory for centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…These findings were replicated in another three studies (Saunders et al, 2012). Zengel et al (2015) conducted two experiments assessing the extent to which participants varied in levels of social anxiety (Social Interaction Anxiety Scale; Rodebaugh, Woods, Heimberg, Liebowitz, & Schneider, 2006). These participants engaged in a modified mnemic neglect paradigm in which some of the behaviours were linked to traits thought to be important to social anxiety.…”
Section: Trait Anxiety and Social Anxietymentioning
confidence: 79%
See 4 more Smart Citations
“…These findings were replicated in another three studies (Saunders et al, 2012). Zengel et al (2015) conducted two experiments assessing the extent to which participants varied in levels of social anxiety (Social Interaction Anxiety Scale; Rodebaugh, Woods, Heimberg, Liebowitz, & Schneider, 2006). These participants engaged in a modified mnemic neglect paradigm in which some of the behaviours were linked to traits thought to be important to social anxiety.…”
Section: Trait Anxiety and Social Anxietymentioning
confidence: 79%
“…Participants who varied in level of dysphoria (Beck Depression Inventory;Beck, Steer, & Garbin, 1988) were exposed to self-referent behavioural feedback (positive vs. negative, relevant to central or peripheral trait dimensions). The results demonstrated a loss of mnemic neglect associated with dysphoria: Participants high in dysphoria had a greater recall rate for self-threatening (negative, central) feedback than those low in dysphoria (but see Zengel et al, 2015, who in subsidiary analyses reported two non-replications of this loss of mnemic neglect in high dysphorics). We note that in Saunders (2011) this loss of mnemic neglect occurred only for feedback that was especially threatening: The effect did not manifest for peripheral negative behaviours, which were relatively low on self-threat.…”
Section: Dysphoriamentioning
confidence: 88%
See 3 more Smart Citations